Understanding the Experiences Lived by Nurses Caring for Patients with COVID-19: A Hermeneutic Approach - Alrasheeday, Awatif Mansoor; Borja, Ma. Venus; Pasay-an, Eddieson; Alshammari, Farhan (UI Scholars Hub, 2023)
Background: Nursing is highlighted among professions that value caring and is perceived as the profession’s heart and soul because of its critical role in providing and delivering high-quality patient care, especially during this coronavirus disease 2019 (COVID-19) pandemic. However, little is understood about the experiences of the frontline workers in caring for persons diagnosed with COVID-19. This study aimed to explore the experiences of nurses in caring for persons diagnosed with COVID-19 inspired by the four lived worlds of van Manen. Methods: The hermeneutic phenomenology was used in nine nurses working in hospitals of Hail region. This study employed a one-to-one interview approach using the Zoom platform, conducted between June and July 2020. Results: Nine nurses articulated their experiences in caring for patients with COVID-19. Six themes emerged within the four lifeworld such as the feeling of vulnerability to COVID-19, time of uncertainties, price of being a hero, social stigma, holistic care, and sense of belongingness. Conclusions: The feeling of vulnerability to COVID-19 infection, time of uncertainties, price of being a hero, social stigma, and sense of belongingness have been understood in the context of lifeworld existential of van Manen. Issues are articulated directly from those who experienced them. Still, revisiting the existing intervention strategies of the government and institution, including regulating negative emotions, reducing related issues, and improving quality of life, is important.